Hermite-Hadamard inequalities for exponential type harmonically $ ( α, s)_{h}$-convex functions - Kemi Apanpa; Adesanmi Mogbademu; Johnson Olalerun (Journal of Mahani Mathematical Research)
In this paper, the authors study and introduce some new integral forms of Hermite-Hadamard inequalities in the form of harmonically convex functions known as exponential type harmonically $ (α, s)_{h}$-convex function. Additionally, several special characteristics of this class of functions are examined. More precisely, the authors provide some properties and characteristics related to the Hermite-Hdamard inequality for harmonically $ (α, s)_{h}$-convex function, applications of this work with certain examples are made to establish results obtained.